Evolução, decomposição e caracterização da pobreza no Brasil, perío-do 1995-2004 - Queiroz, Sabrina Faria de (2007)
This work has poverty in Brazil as its general objective of study. The specific objectives are: a) to evaluate the evolution of some poverty indicators; b) to characterize the poverty according to geographic and population features; c) to analyze poverty according to its determinants: growth and income redistribution , between 1995 (post-implementation of Plano Real) and 2004. The analysis is carried out with the calculation of poverty indexes. The monetary approach was used according to which poverty is assessed as an income shortage. Although poverty multi-dimensional approach has become stronger in recent years, poverty was analyzed in this study only according to its monetary side. According to that approach poverty is defined as lack of capacities, being classified as poor those who do not have the basic capacities to work in the social medium. Therefore, income was taken as a proxy of minimum necessities. Hypotheses were not pre-defined due to the exploratory character of the analysis. The results indicate a reduction in poverty in rural areas that are strategic to the introduction of policies that fight against poverty as well as against its reduction. Those areas also presented themselves quite sensible to variations in growth and income distribution when of the analysis done for the southeast and northeast regions. Besides, poverty was significant among youngsters as well as among younger families that also have to be an aim of social policies.